Synthesis and Characterization of New Oxazepine Compounds and Estimation its Biological Activity - Khudhair Abbas, Abbas; R. Jber, Nasreen (Al-Nahrain Journal of Science, 2020)
This contribution, direct new azo compounds synthesis via coupling benzidine with 4-hydroxy or alkoxy benzaldehyde (A1-A7). Schiff`s bases (B1-B7) were synthesized by condensation of azo compounds (A1-A7) and 2-aminobenzothiazole. New seven compounds of oxazepines derivates (C1-C7) have synthesized via the reaction between phthalic anhydride and Schiff bases, which that previously prepared to produce seven organic compounds as heterocyclic. As well, the oxazepines synthesized have characterized via (FT-IR, and 1HNMR spectroscopy for several of them) and physical properties have recorded. Finally, oxazepine compounds have tested against bacteria two kinds as gram positive and gram negative.